HUMORAL AND CELLULAR IMMUNITY FACTORS IN MYOCARDIAL INFARCTION - V. I. Seledtsov (SPb RAACI, 2014)
he data presented in this review article characterize the key role of alterations in humoral and cellular immunity factors detectable during post-infarction period. According to these data, immune reactivity may define both a level of the myocardial lesion, and a subsequent clinical course of the disease.